2021
DOI: 10.1017/s1755773921000242
|View full text |Cite
|
Sign up to set email alerts
|

Party competition over EU integration: asymmetrical impacts of external shocks across regions?

Abstract: Using Voting Advice Application (VAA) data from the EU Profiler/euandi Trend File, we studied how parties’ positions towards European integration relate to their positions on other important issues, and how this varies across EP elections, and between European regions. We hypothesized that the association between parties’ EU-integration positions and their positions on other issues was affected by the three major crises that hit the European Union (EU) between 2009 and 2019: the economic, migration, and climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The notion of these pan-European parties is closely related to the idea of transnational political space in the EU, which is a common political space in all EU member states. Empirical studies of party competition so far have shown that a common transnational party space does not exist (Huijsmans and Krouwel, 2021): the issue of EU integration, for instance, is interpreted very differently by parties across the EU. It also does not appear to be the case that party spaces are becoming more similar: both the Eurocrisis and migration crisis had asymmetric impact across European party systems.…”
Section: The Appeal Of Pan-european Partiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of these pan-European parties is closely related to the idea of transnational political space in the EU, which is a common political space in all EU member states. Empirical studies of party competition so far have shown that a common transnational party space does not exist (Huijsmans and Krouwel, 2021): the issue of EU integration, for instance, is interpreted very differently by parties across the EU. It also does not appear to be the case that party spaces are becoming more similar: both the Eurocrisis and migration crisis had asymmetric impact across European party systems.…”
Section: The Appeal Of Pan-european Partiesmentioning
confidence: 99%
“…Figure 1C shows two dimensions related to environmentalism. These do not necessarily structure the Dutch political system but are of secondary importance in the European context (Huijsmans and Kouwel, 2021) and may matter for Volt specifically. The horizontal dimension concerns environmentalism in general terms.…”
Section: The Case Of Voltmentioning
confidence: 99%